Alexithymia Has No Clinically Relevant Association With Outcome of Multimodal Treatment Tailored to Needs of Patients Suffering From Somatic Symptom and Related Disorders. A Clinical Prospective Study - de Vroege, Lars; Emons, Wilco H. M.; Sijtsma, Klaas; van der Feltz-Cornelis, Christina M. (Frontiers in Psychiatry, 2018)
Introduction Alexithymia may moderate the effectiveness of treatment and may predict impaired general functioning of patients suffering from somatic symptom and related disorders (SSRD). Aim We compared alexithymia levels in a clinical prospective study with 234 consecutive patients suffering from SSRD from the Centre of Excellence for Body, Mind, and Health, Tilburg using the Bermond-Vorst Alexithymia Questionnaire, with general population norm scores. Second, we explored treatment outcomes of a multimodal treatment tailored to patient needs by Shared Decision Making (SDM) and Patient Related Outcome Monitoring (PROM) in patients with SSRD. Third, we explored whether alexithymia is associated with treatment outcome. Fourth, we explored if the presence of a chronic medical condition (e.g., diabetes mellitus, cardiovascular diseases) affects the association of alexithymia with treatment outcomes. Results Compared to norm scores, SSRD patients showed elevated scores on the subscales identifying, verbalizing, and fantasizing, and on the cognitive dimension. All patients benefited from treatment in terms of anxiety, depression, and physical symptoms. The association of alexithymia with treatment outcome was significant, but the effect size was negligible (range odds ratios 1.02 – 1.25). The association between alexithymia and treatment outcome was stronger in patients suffering from chronic medical conditions compared to patients without chronic medical conditions. However, the effect size of this association was negligible (range odds ratio 0.94 – 1.12). Discussion Alexithymia scores are elevated in patients with SSRD compared with general population scores, but the level of alexithymia has no clinically relevant association with treatment outcome both in SSRD patients with and without comorbid chronic medical conditions.